Wastewater surveillance of SARS-CoV-2 in Austria: development, implementation, and operation of the Tyrolean wastewater monitoring program. (19th January 2022) - Daleiden, Beatrice; Niederstätter, Harald; Steinlechner, Martin; Wildt, Stefan; Kaiser, Manfred; Lass-Flörl, Cornelia; Posch, Wilfried; Fuchs, Stefan; Pfeifer, Bernhard; Huber, Andreas; Oberacher, Herbert
Abstract: Wastewater-based epidemiology (WBE) is an effective approach for tracking information on spatial distribution and temporal trends of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the community level. Herein, the development, implementation, and operation of the wastewater monitoring program serving Tyrol – a federal province of Austria – are described. The development of this program was initiated by Tyrolean health authorities at the end of the first phase of the Coronavirus disease 2019 (COVID-19) pandemic (May 2020). In close co-operation with the water sector and academic institutions, efficient and effective workflows and processes for wastewater surveillance were established. The monitoring program went into operation in November 2020. By the end of July 2021, a total of 5, 270 wastewater influent samples collected at 43 sites were analyzed. The monitoring program provided valuable insights into the development of the pandemic situation in Tyrol and fulfilled several tasks that are of importance in different phases of the pandemic. It represented an early-warning system, provided independent confirmation of temporal trends in COVID-19 prevalence, enabled the assessment of the effectiveness of measures, alerted about bursts of disease activity, and provided evidence for the absence of COVID-19. These findings underline the importance of establishing national wastewater monitoring programs as a complementary source of information for efficient and effective pandemic management. HIGHLIGHTS: The development, implementation, and operation of the Tyrolean SARS-CoV-2 wastewater monitoring program are described. Health authorities are receiving regular updates on the pandemic situation in 43 Tyrolean regions. Turnaround times are <36 hours. Lead times of 3–7 days were observed. Ten positive cases per 120, 000 persons were detectable. Graphical Abstract